2011
DOI: 10.1159/000329623
|View full text |Cite
|
Sign up to set email alerts
|

A 6-Year Experience of 100 Cases of Pediatric Bony Craniovertebral Junction Abnormalities: Treatment and Outcomes

Abstract: The authors studied 100 consecutive cases of pediatric bony craniovertebral junction abnormalities operated between 2001 and 2006. The pathologies were developmental (n = 86), traumatic (n = 10) and tuberculous (n = 4). Surgical procedures included transoral decompression (n = 59), occipitocervical fusion (OCF, n = 69), C1-C2 fusion (n = 22), occiput-C2 wiring (n = 5), and posterior fossa decompression (n = 5). Implants for OCF included contoured stainless steel rods (n = 47), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 37 publications
1
11
0
2
Order By: Relevance
“…8,9,[12][13][14]16,17,19,21,25,32 One type of upper cervical spine injury, atlantooccipital dislocation (AOD), is a severe injury associated with high mortality rates. 1,2,11,12,[16][17][18][19][20]22,24 In postmortem examinations, evidence of AOD is present in 20%-31% of deaths due to cervical spine injuries.…”
mentioning
confidence: 99%
“…8,9,[12][13][14]16,17,19,21,25,32 One type of upper cervical spine injury, atlantooccipital dislocation (AOD), is a severe injury associated with high mortality rates. 1,2,11,12,[16][17][18][19][20]22,24 In postmortem examinations, evidence of AOD is present in 20%-31% of deaths due to cervical spine injuries.…”
mentioning
confidence: 99%
“…By contrast, in their series of 59 cases of ventral cervicomedullary decompression using a transoral approach, Yerramneni et al reported a postoperative CSF leak or meningitis in 5 patients (8.5%). 40 Despite concerns for an elevated risk of unintended durotomy and an increased difficulty of repair when using an endoscopic transnasal approach rather than a transoral approach, limited current data do not support this conclusion.…”
Section: Transnasal Odontoid Resection In the Pediatric Populationmentioning
confidence: 95%
“…7,19,21,28,38 Rates of significant upper respiratory tract edema requiring intervention following transoral approaches have been reported in up to 5% of adults and 4% of children, but this rate may be artificially low due to a more cautious timetable for extubation. 6,9,13,20,26,27,36,39,40 Additionally, an endoscopic transnasal approach may allow for a more prompt return to a normal oral diet. 21,24 The incidence of new-onset dysphagia after a traditional transoral approach ranges from 0%-20% in adults and 0%-4% in the pediatric population, which is not unexpected given the dissection of the posterior pharyngeal tissues that is required.…”
Section: Advantages and Disadvantages Of The Endoscopic Transnasal Apmentioning
confidence: 99%
See 2 more Smart Citations